IFN-Aging: Coupling Aging With Interferon Response - Cao, Wei (Frontiers in Aging, 2022)
Chronic inflammation affects many diseases and conditions, including aging. Interferons are a part of the immune defense against viral infections. Paradoxically, various aging tissues and organs from mammalian hosts perpetually accumulate changes brought by interferon pathway activation. Herein, we connote the mechanisms behind this phenomenon and discuss its implications in age-related pathology.